ANALISIS PERALIHAN HAK ATAS TANAH SECARA DIBAWAH TANGAN TERHADAP OBJEK TANAH YANG MASIH SEBAGAI JAMINAN KREDIT PEMILIKAN RUMAH (KPR) STUDI PUTUSAN MAHKAMAH AGUNG NO. 1142K/Pdt/2014 - Agung Saleh Ritonga; M. Yamin Lubis, Hasim Purba, Suprayitno (INTELIGENSIA MEDIA, 2025)
In order to meet the needs of the community for housing, the role of financial institutions, especially banks, is needed in providing funds for housing development efforts, one of which is through Home Ownership Credit (KPR). Definition of KPR according to Law no. 10 concerning Banking of 1998, is a long-term credit distributed by banks to their debtors to build or own a new or used house on land with the guarantee of a certificate of ownership of the house and land itself. If the transfer of land rights over the mortgage object is carried out through private sale and purchase between the bank debtor and the buyer or third party, it will create new problems for the buyer of the mortgage land or the third party as the recipient of the credit transfer, both in terms of legal certainty and in terms of ownership of the mortgage land. This research method uses a Normative Juridical research type which is descriptive analytical in nature. The data source uses secondary data sources using legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials using secondary data collection techniques and the data collection tool in this research is document study. The results of the research show that the legality of buying and selling land under the hands of land objects that are still used as collateral for home ownership credit (KPR) is legally binding on the seller and buyer as long as they fulfill the terms and conditions of a valid agreement in Article 1320 of the Civil Code, but cannot be recorded or changed the name of the certificate. The legal consequences for private land buyers who buy land objects that are still used as collateral for KPR credit are that these buyers are not protected by the legal provisions of Article 531 of the Civil Code and are not protected by the provisions of national agrarian law, namely Law No. 5 of 1960 concerning Principles Agrarian and derivative implementing regulations. In the Supreme Court Decision Number 1142 K/Pdt/2014, the panel of judges stated that the sale and purchase of land under the hands of the seller and the buyer was invalid for the land object which was still used as mortgage collateral because from the facts of the trial, the object of the dispute was still in the name of the land seller or the old KPR debtor while the land buyer cannot prove that the object of the dispute has been transferred to the name of the buyer so that the panel of judges does not provide legal protection to land buyers who buy land as collateral for the KPR privately.